The Influence of Influencer Marketing on Interest in Purchasing Internet Package Services - Maulidina; Putri, Hidayah Yoanna; Arista, Nabilla Dwi (Journal Boas : Business, Economics, Accounting And Management, 2024)
The phenomenon of using influencer marketing is a form of promotional strategy that has been trending in recent years. The massive use of social media influences the way people make their purchasing decisions. Now people believe in one figure who is considered to have the right opinion. Therefore, this research will discuss the Influence of Influencer Marketing on Interest in Buying Internet Package Services, with a case study of LP3I Medan Polytechnic students who use Telkomsel internet package services. The purpose of this research is to find out whether Influencer Marketing (X) has an influence on Purchase Interest (Y). This research uses indicators from each variable. The indicators of Influencer Marketing are visibility, credibility, attractiveness, power. And indicators of Buying Interest are transactional interest, referential interest, preferential interest and exploratory interest. This research uses quantitative methods with a population of 35 people and a sample of 35 people. Meanwhile, to manage research data using the SPSS version 22 program. Based on the research results, it can be seen that the influencer marketing variable partially has a significant effect on the purchase interest variable as proven in the results of the T test research with a calculated t value of 14.441 > t table 1.692 and a significant value of 0.000 < 0.05. The results of a simple linear regression test which has the equation Y = a + bX shows that the influencer marketing variable shows a coefficient value of 0.914, which means that the influencer marketing variable has a positive influence on the purchase interest variable. The results of the coefficient of determination test show that the value (R Square) obtained is 0.863 (86.3%) indicating that influencer marketing has an influence on purchasing interest of 86.3%.